Les images abîmées : entre iconoclasme, pratiques religieuses et rituels « magiques » - Simona Boscani Leoni (Images Re-Vues)
The contribution focuses on the phenomenon of the manipulated, or even degraded, images in the Alpine regions. In these territories we can find at least three categories of damaged images: the first concerns images damaged and concealed for religious motives; the second, manipulation of the image by scratching or writing on the layers of paint, a phenomenon indicating the believer’s intention of recording his presence in the church and at the same time a sort of ritual physically appropriating the image; in the third type the image is repainted or readapted (for instance, the Counter-reformation’s “prudish vandalism” or the reproduction of the same image in a more modern style). The cases of repainting and integrating paintings in more recent ensembles are evidence of the interest of those commissioning them for their parish, as well as a respect for “effective images”. Studying degraded paintings makes it possible to approach the man/image relationship problem according to an original perspective and to highlight the complexity of the visual arts’ impact in the Christian West throughout many centuries.